THE CONCEPT OF TIME IN PORTRAIT DESCRIPTIONS (Soviet era) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Human life is closely connected with the surrounding world and time. After all, the sunrise and sunset, the change of seasons (summer, spring, autumn, winter) are phenomena beyond the control of human will. If we realize that human consciousness is subject to a space-time framework, it is connected with the processes occurring in it. Therefore, it is an objective phenomenon that time and space frameworks are reflected in artistic expressions created by human consciousness. On the other hand, the place of time in literature has a very deep and objective character. In particular, portrait images in the poetry of poets reflected the spirit of the times and determined the stylistic characteristics of the poets. The article analyzes portrait descriptions in Aitysh of poets who lived during the Soviet period and reflected the new era.
Keywords: poets, aitysh, era, care, propaganda, work.